Exploring the Conceptual Constructs of Learners’ Goal Commitment, Grit, and Self-Efficacy - Han, Zhong (Frontiers in Psychology, 2021)
Although learners’ success in learning has generally been attributed to cognitive factors, non-cognitive issues in education should be taken into consideration in the process of learning which affects learners’ achievement. One of these issues which become popular among researchers in the previous decade is grit that is posited as passion and perseverance thanks to its enduring quality and the other is self-efficacy. Another factor is goal commitment that talks about the way to reach a goal or insistent determinations to achieve a goal. The proposed review attempts to focus on these three factors in regulating students’ learning achievement. Accordingly, some educational suggestions are offered for teachers, students, and syllabus designers.